Stress Corrosion Cracking and Copper Alloy Products - Ocenasek, Vladivoj; Lustinec, Jan (Manufacturing Technology Journal, 2022)
Stress corrosion cracking (SCC) is a common cause of structural failure. The simultaneous action of the corrosive environment and tensile stresses creates cracks that have an intercrystalline or transcrys-talline character. These are cracks with a fragile morphology of the fracture surface without signs of plastic deformation in their vicinity. SCC cracks occur in several alloys. This paper focuses on copper alloys in which this type of failure occurs frequently. Examples from practice show cases where the occurrence of SCC violation was related to the conditions of use of components and their production technologies. The paper does not aim to capture all the influences associated with the occurrence of SCC failure of copper alloy products.
Keywords: SCC stress corrosion cracking; copper alloys; cold deformation; heat treatment; tensile stress; residual stress